The Effect of The Number of Taxable Enterprise, Tax Audit, Tax Collection On Value Added Tax Receiving - Haidarputra, Alferdio; Pahala, Indra; Muliasari, Indah (LPPM Universitas Negeri Jakarta, 2022)
This study aims to provide empirical evidence about the effect of taxable enterprise, tax audits, tax collection on value added tax revenues.This research uses sampling method with saturated sampling technique. The population in this study used all taxable enterprise registered at KPP Pratama Jakarta Setiabudi Empat. The sample used in this study was 36 data using the Time series data type. The statistical method used is multiple linear regression analysis with SPSS calculator. The results of this study indicate that taxable enterprise, tax audits, and tax collection have an effect on value added tax revenues.